Role of budesonide inhalation in treatment of meconium-aspiration syndrome - Zainab S Ahmed; Amira M Mohamed; Mona M Abdelmeguid (Wolters Kluwer Medknow Publications, 2022)
Background and aim Meconium-aspiration syndrome (MAS) is a common cause of respiratory distress. MAS is a serious disease that affects neonates born through meconium-stained amniotic fluid. The pathophysiology of MAS is multifactorial, inflammation has an important role in MAS, so anti-inflammatory drugs like corticosteroids may be effective in the treatment of MAS. Budesonide is a nonhalogenated glucocorticoid that can reduce vascular permeability, inhibit secretion of mucus, relieve edema and spasm, and help pulmonary ventilation. In this study we aimed to find out the effect of early nebulized budesonide in the treatment of MAS. Patients and methods This was a prospective study conducted during the period from October 2017 to July 2018 at El-Minia General Hospital and Al-Azhar University Hospital, Assiut. Intervention: budesonide inhalation in a dose of 50 mg every 12 h till clinical recovery, whichever was earlier. Results The present study revealed that nebulized budesonide improves the clinical outcome of newborns with MAS in terms of lowering the duration of O2 dependency, duration of respiratory distress, duration of hospital stay, duration of radiograph clearance, time for full feeding (P<0.001), and thus early discharge from the NICU. Conclusion Early nebulized budesonide is effective in treating MAS and has high safety with almost no short-term complications.